Desakralisasi Simbol Politheisme dalam Silsilah Wayang: Sebuah Kajian Living Qur’an dan Dakwah Walisongo di Jawa - Syamsul Bakhri; Ahmad Hidayatullah (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2019)
An Wayang is an adoptive creation from the Ramayana Mahabharata epic in the past that certainly full of Hinduism value. Descriptive qualitative research use library study approach aims to find out the desacralization of symbols of polytheism through the composition of wayang lineages. Those data validity is obtained by triangulating data sources, By integrating data from journals and books on wayang lineages then analyzed by the acculturation theory of Koentjaraningrat. The results showed that Walisongo was the creator and composer of wayang in new shape. Gap between Islam and Hinduism, especially on the theological side, polytheism raises the desacralization of symbols of polytheism, through the formation of a new lineage of the wayang. The change also changes the value of the epic Ramayana Mahabharata story that is centered on Trimurti before, to the nasab of the Prophet Sis then the Prophet Adam which is a representation of the symbol of Godmonotheism that does not have children, as writen in Al Qur’an; Changes in the wayang lineage and da'wah were carried out persuasively by Walisongo without causing any conflict in the community, even bloodshed.